Transcatheter versus surgical aortic valve replacement: an updated systematic review and meta-analysis with a focus on outcomes by sex. (25th November 2020) - Dagan, M; Yeung, T; Stehli, J; Stub, D; Walton, A.S; Duffy, S.J
Abstract: Background and purpose: Women at increased surgical risk have been shown to have better outcomes with transcatheter aortic valve implantation (TAVI) as compared to surgical valve replacement (SAVR). With the scope of TAVI moving into low-surgical risk patients we aimed to update the current literature to include the new low-risk randomized controlled trial data in investigating outcomes by sex. Methods: We systematically searched MedlineOVID, PubMed, Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and reference lists for relevant randomised controlled trials (RCTs) comparing TAVI to SAVR published prior to October 7th 2019. Data extraction was performed by two independent authors and included trial design details, baseline characteristics and outcome data stratified by sex. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool. Quantitative synthesis of pooled data was performed using Mantel-Haenszel fixed or random effects model. Q-statistic and the I2 test were used for assessment of heterogeneity. Results: Our search yielded eight RCTs included in the final quantitative synthesis. The overall pooled cohort was 8, 040, of whom 41.4% were female. Women had significantly lower rates of one-year all-cause mortality and one-year composite endpoint with TAVI as compared to SAVR. The selective mortality benefit with TAVI over SAVR in women did not persist to five-years. At 30-days, women demonstrated lower rates of major bleeding and acute kidney injury following TAVI compared to SAVR. For men, these outcomes were similar regardless of type of intervention. Both sexes were at increased risk of major vascular complications with TAVI as compared to SAVR, however women demonstrated nearly double the odds of major vascular complication with TAVI compared to men. Conclusion: Our updated meta-analysis demonstrates that at one-year women undergoing TAVI have significantly lower mortality and better safety outcomes compared to those undergoing SAVR. These benefits are not seen in men. In the new low-risk era, these results are ever more important for guiding appropriate patient selection. Funding Acknowledgement: Type of funding source: None